2012
DOI: 10.1074/jbc.m112.364414
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Cell-specific MicroRNA-15a Inhibits Angiogenesis in Hindlimb Ischemia

Abstract: Background: MicroRNAs mediate angiogenesis in both physiological and pathological conditions, but underlying molecular mechanisms are largely unexplored. Results: Endothelial miR-15a negatively regulates angiogenesis in vivo and in vitro by suppression of FGF2 and VEGF. Conclusion: MiR-15a inhibits endothelial autonomous angiogenesis. Significance: MiR-15a is a negative regulator of angiogenesis and a potential target for the restorative therapy of ischemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 45 publications
3
97
0
Order By: Relevance
“…In the initial RTP, we included 127 genes that are known to be involved in neovascularization from both literature and our own studies (Online Table IA). As anticipated, we observed enrichment of putative binding sites for several microRNAs that were previously reported to influence postischemic neovascularization, including miR-17/92a 9 (29 and 21 putative target genes, respectively), miR-106b/93/25 8,14 (29,29, and 21 putative target genes, respectively), the miR-15a family 10,11,25 (26 putative target genes), miR-503 13 (11 putative target genes), and miR-100 7 (2 putative target genes) but not, for example, miR-126. 6 However, more outspoken was the enrichment of putative binding sites for 27 microRNAs from the 14q32 microRNA gene cluster, including miR-329, miR-494, and miR-495 (20, 31, and 44 putative target genes, respectively).…”
Section: Reverse Target Predictionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the initial RTP, we included 127 genes that are known to be involved in neovascularization from both literature and our own studies (Online Table IA). As anticipated, we observed enrichment of putative binding sites for several microRNAs that were previously reported to influence postischemic neovascularization, including miR-17/92a 9 (29 and 21 putative target genes, respectively), miR-106b/93/25 8,14 (29,29, and 21 putative target genes, respectively), the miR-15a family 10,11,25 (26 putative target genes), miR-503 13 (11 putative target genes), and miR-100 7 (2 putative target genes) but not, for example, miR-126. 6 However, more outspoken was the enrichment of putative binding sites for 27 microRNAs from the 14q32 microRNA gene cluster, including miR-329, miR-494, and miR-495 (20, 31, and 44 putative target genes, respectively).…”
Section: Reverse Target Predictionsupporting
confidence: 50%
“…The authors described an absolute increase in perfusion of 10% to 15% at day 7 after double ligation of the femoral artery in C57BL/6 mice. Finally in 2012, Yin et al 10 took an opposite approach and demonstrated that overexpression of miR-15a attenuates postischemic blood flow recovery, resulting in an absolute decrease of perfusion of 10% at day 7 and 25% at day 14 after excision of the femoral artery, compared with control animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miR-15a/16-1 inhibits the growth of the cancer stem cell population in breast cancer (44). In addition, miR15a/16-1 suppresses angiogenesis by targeting VEGF (45,46). Interestingly, the protooncogene c-MYC, which directly regulates AP4, was shown to repress the transcription of DLEU2, and therefore decrease miR-15a/16-1 expression through direct binding in the vicinity of the two transcription start sites, presumably via recruiting histone deacetylase 3 (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being conjugated to argonaute-2, the miRNAs were found within exosomes, 70 suggesting their potential as markers of critical limb ischemia. Because miR-15a seems to inhibit angiogenesis, 71 it will be interesting to determine whether exosomes actually contribute to ischemic injury in this case. In other situations, the injection of proangiogenic exosomes can be beneficial.…”
Section: Exosomes and Cvdmentioning
confidence: 99%